Everyday life of teachers in the cities of Central Kazakhstan in 1946–1970s - Yeleukhanova, S.V.; Dzhumabekov, Zh.A.; Utebayeva, A.D. (KU Publ., 2022)
The article is devoted to the study of the daily life of teachers in the cities of Central Kazakhstan in 1946–1970s. It is an attempt to assess the role and position of teachers in the social and cultural development of the region’s cities. At the same time, cities had a significant impact on the life of citizens. The relevance of the research topic is due to the fact that in national historiography, the plots devoted to the diversity of citizens types of Central Kazakhstan, their everyday life in the designated period have not been sufficiently studied. The study is based on a comparison of reference images and everyday practices, the public life of urban teachers in the region. Materials of teachers’ memoirs, interviews of former students, townspeople of different professions about teachers of the period 1946–1970s are analyzed according to such parameters as appearance, including clothes, hairstyle, behavior, the language of everyday communication, professional qualities, living conditions, and the influence of the ideological factor. The social status, nature and working conditions, the ideological guidelines of the state singled out teachers from the urban environment, formed their special psychology and self-awareness. The article is written within the framework of one of the modern trends in historical science - the history of everyday life. The authors conclude that teachers, in comparison with the diverse types of citizens of Central Kazakhstan (1946– 1970s), had both common and specific features and characteristics. Their analysis has not only cognitive, but also theoretical value. The materials of the article can become a conceptual basis for studying the daily life of citizens belonging to different professional or social groups.
1946-1970 жж. Орталық Қазақстан қалаларының ұстаздарының күнделікті өмірі
Повседневная жизнь педагогов городов Центрального Казахстана в 1946 – 1970-е годы
Keywords: townspeople; teachers; urban space; urban everyday life; city; everyday practices; memories; Central Kazakhstan; USSR